Investigating differences between tamoxifen resistant and sensitive breast cancer cells with flow cytometry. Issue 2 (28th January 2021) - Bitton, Aric; Zheng, Yan; Houston, Jessica P.; Houston, Kevin D.
Abstract: The active metabolite of tamoxifen, 4‐hydroxytamoxifen, functions as an anti‐estrogen in breast cancer cells and thus inhibits proliferation. While tamoxifen continues to be successfully used to treat estrogen‐dependent breast cancer, most patients receiving treatment will develop chemoresistance over time. Two commonly reported biomarkers of tamoxifen resistance are decreased expression of insulin‐like growth factor 1 receptor (IGF‐1R) and increased expression of epidermal growth factor receptor (EGFR). In prior work we have shown that these receptors facilitate chemoresistance and have unique regulatory functions measurable in resistant cell lines compared with nonresistant. Thus, we hypothesized that these receptors and a newly identified biomarker, integrin β1, may be used to search for the presence of resistant breast cancer cells within a population of cells that are sensitive to tamoxifen therapy. We tested this by designing a straightforward cell‐labeling approach to measure differences in the receptor expression of resistant vs. sensitive cells cytometrically. Our results show that separation is possible when observing the expression of IGF‐1R as well as integrin β1. Interestingly, we found no detectable difference in EGFR expression between tamoxifen resistant and ‐sensitive cells when measured with cytometry despite the fact that EGFR is upregulated in resistant cells. Our long‐term goal is to utilize sorting to isolate tamoxifen resistant subpopulations of cells by receptor expression level. Isolating rare resistant cells that reside within a population of drug‐sensitive cells will offer new insights into why chemoresistance occurs.